1996
DOI: 10.1002/j.1460-2075.1996.tb01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of the yeast poly(A) tail binding protein with translation initiation factor eIF-4G.

Abstract: Although the cap structure and the poly(A) tail are on opposite ends of the mRNA molecule, previous work has suggested that they interact to enhance translation and inhibit mRNA degradation. Here we present biochemical data that show that the proteins bound to the mRNA cap (eIF‐4F) and poly(A) tail (Pab1p) are physically associated in extracts from the yeast Saccharomyces cerevisiae. Specifically, we find that Pab1p co‐purifies and co‐immunoprecipitates with the eIF‐4G subunit of eIF‐4F. The Pab1p binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
629
0
3

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 652 publications
(660 citation statements)
references
References 23 publications
(38 reference statements)
28
629
0
3
Order By: Relevance
“…We did, however, observe a complete loss of the PABP that co-puri®ed with eIF4E after antiFas treatment (Figure 9c; compare lanes 5 and 6). The latter result may indicate that PABP associates with eIF4G in mammalian eIF4F complexes, as is the case in yeast (Tarun and Sachs, 1996;Le et al, 1997), or that interaction of PABP with the eIF4G homologue PAIP (Craig et al, 1998) is also altered in cells undergoing apoptosis. The e ects of anti-Fas treatment on eIF4G and the co-puri®cation of PABP with eIF4E were blocked by Z-VAD.FMK (Figure 9c, lanes 2 vs 3 and lanes 6 vs 7), under conditions where this agent prevented the apoptotic response as measured by PARP cleavage (Figure 9a) or the appearance of cells with less than the G1 content of DNA (Figure 9b).…”
Section: Induction Of Apoptosis In Jurkat Cells Results In Loss Of Eif4gmentioning
confidence: 93%
See 1 more Smart Citation
“…We did, however, observe a complete loss of the PABP that co-puri®ed with eIF4E after antiFas treatment (Figure 9c; compare lanes 5 and 6). The latter result may indicate that PABP associates with eIF4G in mammalian eIF4F complexes, as is the case in yeast (Tarun and Sachs, 1996;Le et al, 1997), or that interaction of PABP with the eIF4G homologue PAIP (Craig et al, 1998) is also altered in cells undergoing apoptosis. The e ects of anti-Fas treatment on eIF4G and the co-puri®cation of PABP with eIF4E were blocked by Z-VAD.FMK (Figure 9c, lanes 2 vs 3 and lanes 6 vs 7), under conditions where this agent prevented the apoptotic response as measured by PARP cleavage (Figure 9a) or the appearance of cells with less than the G1 content of DNA (Figure 9b).…”
Section: Induction Of Apoptosis In Jurkat Cells Results In Loss Of Eif4gmentioning
confidence: 93%
“…Recently a second form of human eIF4G has also been described (Gradi et al, 1998). eIF4G possesses domains for the binding of eIF4E and eIF3 in the N-terminal and central parts of its sequence respectively, and it also has binding sites for eIF4A (Lamphear et al, 1995; and, at least in yeast, for the poly(A) binding protein (PABP) (Tarun and Sachs, 1996;Le et al, 1997;Tarun et al, 1997). Interaction of PABP with eIF4G or with the recently discovered eIF4G homologue PAIP (Craig et al, 1998) may allow functional association of the 3' end of an mRNA with the 5' end, thus e ectively causing`circularization' of the mRNA during protein synthesis (Tarun et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a poly(A) tail is generally thought to be a critical determinant of mRNA stability+ For some mRNAs, poly(A) shortening or removal is the ratedetermining event in their decay, whereas, for others, it may be an obligate event in their degradation, but it is not the rate-determining step (Chen et al+, 1995;Caponigro & Parker, 1996;+ The presence of a poly(A) tail provides an mRNA with a binding site for poly(A)-binding protein, which, in turn, serves to promote translational initiation and antagonize mRNA decapping in the cytoplasm (Gallie et al+, 1989;Caponigro & Parker, 1995;Tarun & Sachs, 1996)+ In this study, the TRP4-ribozyme allele produces a transcript lacking a poly(A) tail and, as a consequence, it would be predicted that this mRNA would be susceptible to nucleolytic attack and considerably less abundant than its wild-type counterpart+ In contrast, we found that the nonpolyadenylated ribozyme transcript accumulated to levels indicative of little, if any, change in stability+ Maintenance of the stability of the poly(A)-deficient TRP4-ribozyme mRNA is likely to be a result of the action of the ribozyme in generation of the mRNA 39 end, and not to some internal TRP4 sequence features, as deletion of the TRP4 39 UTR resulted in a significant decrease in the amount of TRP4 mRNA+ In support of this idea, a previous study determined that the presence of a ribozyme in an mRNA is not sufficient to render it more labile (Donahue & Fedor, 1997)+ Several plausible explanations could account for the unchanged stability of TRP4-ribozyme mRNA+ The secondary structure formed by the hammerhead ribozyme, or the terminal 29-39cyclic phosphate (Tanner, 1999), instead of a 39-OH, might impede the accessibility of 39 exonucleases to the mRNA+ Alternatively, the absence of a poly(A) tail might uncouple an otherwise linked mechanism in which decapping is triggered by deadenylation (Muhlrad et al+, 1994)+ A more likely explanation is that degradation of the TRP4 mRNA is normally associated with its translation (Jacobson & Peltz, 1996)+ In a manner previously exemplified by the MATa1 mRNA (Parker & Jacobson, 1990), impaired translation of the TRP4-ribozyme mRNA (see below) may reduce the extent to which ribosome-associated factors act to promote decay+…”
Section: Discussionmentioning
confidence: 99%
“…(69)(70)(71)(72) In a yeast cell-free system, the poly(A) tail, like the cap structure, was able to support the recruitment of the 40S ribosomal subunit by itself to an uncapped mRNA. (73) This function of the poly(A) tail as well as the functional synergy with the cap structure requires the poly(A)-binding protein (PABP) (73) and its interaction with the N-terminal part of eIF4G (74,75) (Fig. 3).…”
Section: Assembly Of the 80s Ribosomementioning
confidence: 99%